The Challenges of Data Collection in Rural Dwelling Samples - Carolyn S. Pierce; Elizabeth Scherra (Rural Nurse Organization; Binghamton University, 2004)
Data collection in rural areas presents unique problems that impact the research process and thus the outcomes of the research. Some of the issues that must be accounted for include utilization of appropriate tools when studying rural dwelling persons, location of appropriate participants, rural health issues, environmental barriers, and ethical considerations. Researchers must be aware of these unique problems and issues and consider the impact of these issues on the integrity of the data.